Efficient removal of amoxicillin, ciprofloxacin, and tetracycline from aqueous solution by Cu-Bi2O3 synthesized using precipitation-assisted-microwave - Sa'adah, Fatkhiyatus; Sutanto, Heri; Hadiyanto, Hadiyanto; Alkian, Ilham (Communications in Science and Technology, 2024)
This study investigates the synthesis and characterization of Cu-Bi2O3 for degradation of antibiotics AMX, CIP, and TC using precipitation-assisted-microwave method at varying concentrations of Cu at 0%, 2%, 4%, 6%, and 8%. The effect of Cu concentration on the structural, morphological, and optical properties were studied by XRD, UV-Vis, and SEM-EDX. The optimal results were obtained by adding 4% Cu to the Bi2O3 matrix. With an energy band gap of 2.32 eV, a crystal size of 37.04 nm, and ?-Bi2O3 and CuBi2O4 phases. The removal efficiency of each antibiotic using the photocatalytic method varies, with AMX at 52.06%, CIP at 61.72%, and TC at 69.44%. Cu-Bi2O3 degraded TC-type antibiotics more rapidly. The high removal efficiency and rapid reaction rate indicate that Cu-Bi2O3 is an effective antibiotic removal agent. This further confirms the fact that the addition of Cu to Bi2O3 material can increase its ability to degrade antibiotics more effective.